Eyes are essential for magnetoreception in a mammal - Caspar, Kai R; Moldenhauer, Katrin; Moritz, Regina E; Němec, Pavel; Malkemper, E Pascal; Begall, Sabine (Journal of the Royal Society, Interface, 2020)
Several groups of mammals use the Earth's magnetic field for orientation, but their magnetosensory organ remains unknown. The Ansell's mole-rat (Fukomys anselli, Bathyergidae, Rodentia) is a microphthalmic subterranean rodent with innate magnetic orientation behaviour. Previous studies on this species proposed that its magnetoreceptors are located in the eye. To test this hypothesis, we assessed magnetic orientation in mole-rats after the surgical removal of their eyes compared to untreated controls. Initially, we demonstrate that this enucleation does not lead to changes in routine behaviours, including locomotion, feeding and socializing. We then studied magnetic compass orientation by employing a well-established nest-building assay under four magnetic field alignments. In line with previous studies, control animals exhibited a significant preference to build nests in magnetic southeast. By contrast, enucleated mole-rats built nests in random magnetic orientations, suggesting an impairment of their magnetic sense. The results provide robust support for the hypothesis that mole-rats perceive magnetic fields with their minute eyes, probably relying on magnetite-based receptors in the cornea.
Keywords: magnetic sense; magnetite; Magnetics; magnetismus; mole-rat; Magnetic Fields; orientace; lokomoce; Mole Rats; sensory biology; animal orientation; Animals; Orientation; magnetické pole; zvířata; Locomotion; mikroftalmičtí podzemní hlodavci